Innovation and Creativity: Is there economic significance to the creative city ? - Cohendet, Patrick; Zapata, Salomon (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2009)
AbstractThis article aims at defining the concept of creative city. It attempts to clarify the notions of creativity, innovation and invention, often used interchangeably in academic or professional debates. It is argued that creativity does not result from the talents of a few individuals, but that it nourishes itself from the repeated exchanges among a variety of heterogeneous entities that contribute in their own way to foster the development of new ideas. Creative cities can be considered as specific innovative clusters that allow the creative process to be fully expressed, illustrated by the case studies on Montréal and Barcelona.